2018
DOI: 10.1016/j.ajoc.2017.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Acute-onset endophthalmitis caused by Staphylococcus lugdunensis

Abstract: PurposeTo report a series of patients with acute-onset bacterial endophthalmitis caused by culture proven Staphylococcus lugdunensis, and to characterize clinical outcomes and microbiologic susceptibilities of this organism.ObservationsThe study included six eyes of 6 patients. The etiologies included cataract surgery (3), open globe injury (2), and intravitreal injection (1). Isolates of S. lugdunensis demonstrated sensitivity to vancomycin in all cases reported. Three of 6 isolates of S. lugdunensis demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
(11 reference statements)
0
9
0
Order By: Relevance
“…Endophthalmitis caused by S. lugdunensis however has only been described in a very few cases, with its nature differing depending on the type of procedure causing it. In one study, it was found that when endophthalmitis was caused by intraocular surgery, it had an insidious presentation with good visual outcomes after treatment [9]. However, when caused by intravitreal injections, there was a more acute and aggressive course with poor visual outcomes after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Endophthalmitis caused by S. lugdunensis however has only been described in a very few cases, with its nature differing depending on the type of procedure causing it. In one study, it was found that when endophthalmitis was caused by intraocular surgery, it had an insidious presentation with good visual outcomes after treatment [9]. However, when caused by intravitreal injections, there was a more acute and aggressive course with poor visual outcomes after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[2] The majority of S. lugdunensis endophthalmitis reported cases are characterized by an insidious onset – an average of 1 week after intraocular procedure: cataract surgery, intravitreal injections, or open globe repairs. [34] There are also S. lugdunensis endophthalmitis cases following intravitreal injections with early onset as presented by Murad-Kejbou et al . with aggressive course of disease leading to poor visual outcomes ranging from 6/30 to hand movements.…”
Section: Discussionmentioning
confidence: 99%
“…has shown that postcataract surgery S. lugdunensis endophthalmitis cases are characterized by a worse final functional prognosis and have a higher risk of postvitrectomy retinal detachment compared with other coagulase-negative Staphylococcus endophthalmitis cases as the organism causes more necrozis and thereby retinal detachment. [3] Silicon oil is known to have antibacterial properties and several studies have shown the benefit of silicon oil in endophthalmitis cases without retinal detachment. [10] Taking in consideration the above facts, filling the eye with silicon oil in our case was a logical approach and the final visual acuity of 6/36 after silicon oil removal was more than we have hoped for.…”
Section: Discussionmentioning
confidence: 99%
“…The predilection for each site varies with age. S. lugdunensis have been reported to cause many other infections like native and prosthetic valve endocarditis, osteomyelitis, prosthetic joint infections, endophthalmitis [ 6 ], foreign body-associated infection involving ventriculoperitoneal shunts [ 7 ], peritoneal dialysis catheters [ 8 ], hemodialysis catheters, and external ventricular drains [ 9 ].…”
Section: Introductionmentioning
confidence: 99%